2021
DOI: 10.1111/jfb.14734
|View full text |Cite
|
Sign up to set email alerts
|

Observations of growth changes during the embryonic‐larval‐transition of pikeperch (Sander lucioperca) under near‐natural conditions

Abstract: Sander lucioperca is an organism of growing importance for the aquaculture industry.Nonetheless, the rearing of S. lucioperca larvae is proving to be a difficult task as it is facing a high mortality rate during hatching and the change to exogenous feeding. To gain insight into growth patterns during this period, the authors analysed pikeperch embryos and larvae from 9 days before hatching to 17 days after hatch. Hereby they were able to describe a natural development by using close to natural conditions based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Similarly, a study with a focus on skeletal development demonstrated an intermediate reduction in size increase for individual pikeperch reared in environments with constant temperatures [10]. As a result of these studies, a distinct early larval growth phase with a low to no size increase can be differentiated from a later larval growth phase with increasing size variants [9,10]. Based on the occurrence of characteristic ontogenetic events, these groups can be attributed to the larval stages L1 to L2 (early larval group) as well as L3 to L6 (late larval group) described by Pe ňáz [11].…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Similarly, a study with a focus on skeletal development demonstrated an intermediate reduction in size increase for individual pikeperch reared in environments with constant temperatures [10]. As a result of these studies, a distinct early larval growth phase with a low to no size increase can be differentiated from a later larval growth phase with increasing size variants [9,10]. Based on the occurrence of characteristic ontogenetic events, these groups can be attributed to the larval stages L1 to L2 (early larval group) as well as L3 to L6 (late larval group) described by Pe ňáz [11].…”
Section: Introductionmentioning
confidence: 85%
“…The growth of pikeperch larvae does not occur steadily during development. A previous study described different phases of growth occurring during the larval development of pikeperch reared in a semi-natural environment [9]. Similarly, a study with a focus on skeletal development demonstrated an intermediate reduction in size increase for individual pikeperch reared in environments with constant temperatures [10].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations